Kelios pastabos apie sosto vaizdavimą XIV amžiaus pabaigos- XV amžiaus vidurio Lietuvos valdovų sfragistikoje - Skurvydaitė, Loreta (Lietuvos istorijos studijos, 2009)
Gediminas used a majesty seal which reflected the ruler's political objective. Gediminas' majesty seal is known only from the description, which reveals that the ruler holds the sovereign crown in his hand. The ruler is sitting in a cathedra. This description does not give us much space for consideration. We know that this seal was most probably made by Riga's gravers. Gediminas' attempts for christening, which would open the way to the change of the state rank, don't contradict the presumption that the majesty seal contained royal insignias, although there is no information about the throne.The majesty seals of Vytautas and later Žygimantas Kęstutaitis show the ruler's throne, which is quite archaic for the beginning of the XV century. This could be explained by two presumptions: either the seals of Vytautas and Žygimantas Kęstutaitis reflected the real throne of that period, or his rank of the grand duke didn't allow him to use the same pictorial tradition, which is visible in Jogaila's majesty seal.